Adubação do crambe com dejetos de animais - Pereira, Natalia (2017)
The insertion crambe (Crambe abyssinica Hochst ex R.E.Fr.) on the production systems wich be of no tillage crop makes possible the residual fertilizations harnessing of the previously implanted crop. Generally, on the most production systems, the nutrition offer for the plants is made by chemical fertilizations that represents majority of the production costs. One alternative to reduce the costs and to provide qualitys nutrients is by the waste animals utilization. The aim of this study is evaluated the harnessing nutrient level of the residues extracted by crambe and its productive performance after the crop bean fertilizated with different doses application of poultry litter, pig slurry and chemical fertilization. The experimental area is located at the Experimental Station of the Agronomic Institute of Paraná, in Santa Tereza do Oeste - PR. The treatments were generated by factorial (2x3)+1+1, being two waste (liquid swine and poultry litter) with three doses of each (poultry litter: 3.3, 6.6 and 9.9 t/ha (wet basis) and pig slurry: 60,120 and 180 m3/ha. Others additional treatments were the control (no fertilization) and mineral fertilization (215 kg/ha of the formulated 08-28-16). Was evaluated the leaf content of nitrogen, phosphorus, potassium, copper and zinc, the lodging, grain yield and oil yield. The data were submitted to variance analysis (ANOVA); the effect and kind of animal waste were evaluated by the Tukey test with 5 % of probability; and the adicional treatments were compared by contrast analysis. The residual fertilizers with animal manure results in crambe plant with bigger leaf content of P and Zn. And also was a bigger percentation of lodging in relation to control and mineral residual fertilization. The grain productivity and oil yeld was equivalent, compared with residual fertilization with animals waste and mineral.